Sistem Informasi Pengelolaan Kas Berbasis Web di Masjid Al.Madinah Tangerang - Ambo, Takdir; Hati, Kusuma (LPPM Universitas Islam 45 Bekasi, 2019)
Abstract Al-Madinah Mosque has carried out its functions and roles in the management of mosques. But it still needs information system because so far it is still use conventional system. So it is rather difficult to provide information about cash flow. in reporting on mosque finance. The purpose of this website-based system design is to facilitate mosque administrators in delivering information on cash in and cash out reports, to facilitate mosque administrators in delivering mosque financial information to the public, to design systems that are easy to use and can carry out accurate data collection.The information system designed contains data on positions, clerk data, user data, cash-in data, cash out data, print data officers and print cash data. While the tools used to build this system are using the PHP programming language with the MySQL database. Keywords: Cash flow, Information system, Report Abstrak Masjid Al-Madinah telah melaksanakan fungsi dan peranannya dalam manajemen pengelolaan masjid. Tetapi masih membutuhkan sebuah sistem informasi karena selama ini masih bersifat konfensional. Sehingga agak kesulitan dalam memberikan informasi mengenai arus kas dalam pelaporan keuangan Masjid. Maksud dari rancang bangun sistem berbasis website ini, yaitu : untuk mempermudah pengurus masjid dalam penyampaian informasi laporan kas masuk dan kas keluar, untuk mempermudah pengurus masjid dalam penyampaian informasi keuangan masjid ke masyarakat, untuk merancang sistem yang mudah digunakan dan dapat melakukan pendataan dengan akurat. Sistem informasi yang dirancang berisi tentang data jabatan, data petugas, data user, data kas masuk, data kas keluar, cetak data petugas dan cetak data kas. Sedangkan tools yang digunakan untuk membangun sistem ini adalah menggunakan menggunakan bahasa pemrograman PHP dengan database MySQL. Kata kunci: Arus kas, Sistem Informasi, Laporan